(untitled) (Acta Scientiarum. Education, 2014)
The study assesses the quantity and quality of lecturers for effective implementation of the NCE Physics curriculum in the Federal andStateCollegesof Education inNigeria. The sample was drawn from twoFederalCollegesof Education and twoStateCollegesof Education in all the six geo-political zones inNigeria. 60 lecturers were purposively sampled from 24 colleges of education. The instrument used was Lecturers’ questionnaire (LVENPC). Frequency counts, percentages, charts and chi-square analysis were applied to test the hypothesis. The result indicates that there are no enough lecturers in both Federal and State Colleges of Education and the quality of the lecturers is appropriate, there is no significant difference in the staffing of lecturers’ from Federal and State Colleges of Education on the quantity and quality of human resources for successful implementation of Physics course. It was recommended that sufficient Physics lecturers should be employed to teach Physics in Colleges. Colleges should ensure sufficient provision of human resources in both quantity and quality to enable the objectives of the programme to be fully achieved.